Exploring Contributing Factors to Environmental Disclosures in Islamic Commercial Banks of Indonesia - Hanifah, Sarah Hana; Widiyanti, Dwi Retno (Maliki Islamic Economics Journal, 2023)
This study aims to provide an overview and analysis of the influence of policy and corporate governance, including Sharia supervisory board, firm size, firm age, and leverage on green banking disclosure in Islamic commercial banks in Indonesia from 2017 to 2021. This study uses a quantitative approach with panel data regression analysis to examine the causal relationship between the independent variables (policy, board size, board of commissioners, Sharia Supervisory Board, firm size, firm age, and leverage) and green banking disclosures. Islamic commercial banks registered with FSA and IDX are the study population. The sampling method in this study was purposive sampling, with a total sample of six Islamic commercial banks for five years of research. The results of this study show that the company's age, the size of the company, the size of the board of directors, and the board of commissioners have a significant effect on the disclosure of green banking. Meanwhile, Sharia board and leverage do not significantly affect green banking disclosure. This study implies that applying green banking to overcome environmental problems can only be realized by regulation alone, considering the importance of other factors from the bank's side.